Early Life Microbial Exposure and Immunity Training Effects on Asthma Development and Progression - Cereta, Andressa Daronco; Oliveira, Vinícius Rosa; Costa, Ivan Peres; Guimarães, Letícia Lopes; Afonso, João Pedro Ribeiro; Fonseca, Adriano Luís; Sousa, Alan Robson Trigueiro de; Silva, Guilherme Augusto Moreira; Mello, Diego A. C. P. G.; Oliveira, Luis Vicente Franco de; da Palma, Renata Kelly (Frontiers in Medicine, 2021)
Asthma is the most common inflammatory disease affecting the lungs, which can be caused by intrauterine or postnatal insults depending on the exposure to environmental factors. During early life, the exposure to different risk factors can influence the microbiome leading to undesired changes to the immune system. The modulations of the immunity, caused by dysbiosis during development, can increase the susceptibility to allergic diseases. On the other hand, immune training approaches during pregnancy can prevent allergic inflammatory diseases of the airways. In this review, we focus on evidence of risk factors in early life that can alter the development of lung immunity associated with dysbiosis, that leads to asthma and affect childhood and adult life. Furthermore, we discuss new ideas for potential prevention strategies that can be applied during pregnancy and postnatal period.